EnTraP: A factorial randomised controlled trial embedded within world hip trauma evaluation eight COPAL investigating the effect of an enhanced trainee principal investigator package and digital nudge on recruitment rates. Issue 2 (March 2022) - Agni, NR; Fairhurst, C; McDaid, C; Reed, MR; Torgerson, DJ
Background: Randomised controlled trials (RCTs) often struggle with various aspects of participant recruitment, including engaging clinicians to recruit effectively, and subsequently fail to reach their target sample size. Studies evaluating interventions to improve recruitment aimed specifically at recruiters to the trial are limited in number. The RCTs embedded into the World Hip Trauma Evaluation (WHiTE) cohort study use Trainee Principal Investigators (TPIs) to help manage and drive recruitment at trial sites. No formalised training or support is provided by central trials units to the TPIs. Additionally, trial recruiters receive a generic automated email confirming randomisation to the trial with no other communication to influence or incentivise their behaviour to further recruit. The primary aim of this factorial trial was to evaluate the effectiveness of an educational intervention to TPIs and a positive reinforcement intervention via an email (digital) nudge on increasing recruitment. Secondary aims included feasibility of implementing the interventions and surveying TPIs on the educational package quality of content, delivery and ongoing support. Design: This was a multicentre, open, cluster, 2x2 factorial RCT embedded in the WHiTE 8 COPAL RCT, in which research sites were randomised 1:1:1:1 to receive the enhanced TPI package, the digital nudge intervention, both, or neither. Results: 1215 patients were recruited to the WHiTE 8 COPAL trial across 20 sites during the SWAT between August 2018 and March 2019. There was a statistically significant interaction between the interventions (IRR 2.09, 95% CI 1.64 to 2.68, p < 0.001). There was a statistically significant benefit on recruitment (IRR 1.23 95% 1.09 to 1.40, p =0.001) from utilizing an enhanced TPI education intervention. The digital nudge intervention had no significant impact on recruitment (IRR 0.89 95% CI 0.79 to 1.01, p =0.07). Within enhanced TPI package sites, the digital nudge had a beneficial effect, while in the standard practice TPI sites it had a detrimental effect. Feasibility analysis showed the median time to site digital nudge and enhanced TPI set up were one day and 17 days, respectively. 353 digital nudges were created taking an average of 12 min to construct, log the activity and then disseminate to recruiters. Median induction time for enhanced TPI was 32 min and 100% of the groups were extremely satisfied with the induction content, delivery and ongoing support. Discussion: An education and support programme targeted at surgical TPIs involving a digital education package, 1:1 telephone induction and subsequent support package was effective in increasing recruitment in the first 6 months of trial commencement. There was no evidence for the effectiveness of the digital nudge intervention in isolation, although our results show that when combined with an education programme, it leads to enhanced effectiveness of that programme.